Using ORRT Models for Mean Estimation under Nonresponse and Measurement Errors in Stratified Successive Sampling - Monica Choudhary; Sanam Preet Kour; Sunil Kumar; Carlos N. Bouza; Agustín Santiago (Journal of Probability and Statistics)
In the context of a sample survey, the collection of information on a sensitive variable is difficult, which may cause nonresponse and measurement errors. Due to this, the estimates can be biased and the variation may increase. To overcome this difficulty, we propose an estimator for the estimation of a sensitive variable by using auxiliary information in the presence of nonresponse and measurement errors simultaneously. The properties of the proposed estimators have been studied, and the results have been compared with those of the usual complete response estimator. Theoretical results have been verified through a simulation study using an artificial population and two real-life applications. With the outcomes of the proposed estimator, a suitable recommendation has been made to the survey statisticians for their real-life application.